Use of thermal power plants by new world vultures (cathartidae) as an artifice to gain lift - Freire, Davi Almeida; Gomes, Felipe Bittioli Rodrigues; Novaes, Weber Galvão; Cintra, Renato (Wilson Journal of Ornithology, 2015)
Because of recent increases in populations of Black Vultures (Coragyps atratus) and Turkey Vultures (Cathartes aura), vulture-human conflicts have become more common. We can begin to mitigate these conflicts by first identifying what attracts these birds. We investigated the use of thermal power plants (TPPs) by vultures in Manaus, Central Amazon, Brazil, from February-September 2012, and monitored six TPPs throughout urban areas. We visited each TPP six times at three intervals. At all TPPs, we observed vultures use artificial thermals as a way to gain elevation during flight. The largest number of vultures was observed in TPPs near feeding sites and roosting areas. We recorded the largest concentration of vultures in the late afternoon. We observed an interaction effect between site and time, where TTPs near roost sites had more vultures early morning and late afternoon, while TPPs near feeding sites had more vultures at mid-day. Our results show that vultures intensively use TPPs to aid their flight, and this behavior is used mainly at those times under the lowest natural thermals and when the vultures are moving from feeding sites to roosts in the late afternoon. © 2015 by the Wilson Ornithological Society.
Keywords: Bird; Feeding Behavior; Flight Activity; Population Growth; Power Plant; Roost Site; Thermal Power; Urban Area; Amazonas; Manaus; Aves; Cathartes; Cathartes Aura; Cathartidae; Coragyps; Coragyps Atratus